Safeguarding wildlife and human life: Rangers as first responders - Kayla Werner; Rohit Singh; Chris Galliers (Parks)
Rangers' role as emergency first responders is becoming increasingly important in the face of escalating climaterelated natural disasters and extreme weather events. Drawing on a review of literature and data collected from surveys and focal group discussions, this study explores rangers' role as first responders in Asia. A total of 52 rangers from 12 countries were surveyed, revealing the diverse expectations, responsibilities and challenges rangers are facing. Of these, 59.6 per cent of rangers had experienced increased responsibilities during a disaster, including evacuations, rescue and recovery operations, and delivery of essential supplies like food and water. Despite their essential contributions, a majority (over 60 per cent) of rangers surveyed had not received training on first aid, flood response, emergency evacuation or disaster response. Although results varied by specific issue, overall findings indicate an urgent need for policy changes to professionalise the ranger workforce, improve training and access to resources, and establish institutional support systems for rangers. Highlighting rangers' contributions outside of conservation increases visibility of the unique value rangers add in other sectors like public health and safety.